2017
DOI: 10.1634/theoncologist.2016-0272
|View full text |Cite
|
Sign up to set email alerts
|

Health Care Resource Utilization and Associated Costs Among Metastatic Cutaneous Melanoma Patients Treated with Ipilimumab (INTUITION Study)

Abstract: The objective of this study was to describe health care resource utilization and health care costs associated with the management of advanced melanoma patients receiving ipilimumab.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 25 publications
1
12
0
2
Order By: Relevance
“…Before 2011, when a series of innovative drugs in metastatic melanoma patients began reaching the market, medical costs were lower due to limited treatment options [19][20][21]. The cost associated with new therapies for melanoma both immunotherapies and targeted therapies, are the major driver of an increase in the total cost of managing melanoma compared to the situation before 2011 [30].…”
Section: Discussionmentioning
confidence: 99%
“…Before 2011, when a series of innovative drugs in metastatic melanoma patients began reaching the market, medical costs were lower due to limited treatment options [19][20][21]. The cost associated with new therapies for melanoma both immunotherapies and targeted therapies, are the major driver of an increase in the total cost of managing melanoma compared to the situation before 2011 [30].…”
Section: Discussionmentioning
confidence: 99%
“…Drug administration costs per dose were estimated from rates extracted from local Hong Kong data. The model also incorporated costs for routine oncology office visits, lab tests, scans and other resources used in the different health states based on the INTUITION study (see Table 1) [11]. The model also included a one-time cost of terminal care to approximate health care cost in the last 6 months of life as estimated in Wong et al 2007 [12].…”
Section: Costsmentioning
confidence: 99%
“…The Swedish study estimated higher costs, despite expensive new drugs used in patients with metastases not being included. Another multicentre international study 8 conducted after the introduction of ipilimumab on realworld data only for advanced-stage disease showed that the average costs of care for patients with melanoma are lower in Italy than in other European countries: €11 696 in Germany, €6748 in Spain and €3746 in Italy. These differences may be due, for example, to different national health policies and price negotiations of drugs or devices, and to the different overall production costs of hospital or ambulatory care.…”
Section: Conflicts Of Interest: None To Declarementioning
confidence: 99%